Cystic Fibrosis and New Trends by Ophthalmological Evaluation: A Pilot Study. (15th July 2014) - Nebbioso, Marcella; Quattrucci, Serena; Leggieri, Emanuela; Spadea, Leopoldo; Vingolo, Enzo Maria
Abstract : Background. Cystic fibrosis (CF) is characterized by hypoxia that affects several organic tissues. Retinal ganglion cells may suffer from the hypoxic status, and this may lead to alterations of retinal nerve fiber. Methods. Twenty-two eyes in CF patients were analyzed. A complete ocular evaluation and visual field exams of the 30 central degrees were performed using the frequency doubling technology (FDT). Forced expiratory volume in one second (FEV1%), forced vital capacity (FVC%), oxyhaemoglobin saturation (SpO2 %), and hematocrit (Ht%) have been calculated. FDT analyzed parameters were mean deviation (MD) and pattern standard deviation (PSD). Pearson's correlation was chosen as statistical analysis. Results. Data showed statistically significant relationship between MD and Ht% (r value −0.18; P = 0.04 ), MD and FEV1% (r value −0.68; P = 0.001 ), and MD and FVC% (r value −0.45; P = 0.005 ). Moreover, there were correlations between PSD and Ht% (r value 0.29; P = 0.03 ), PSD and SpO2 % (r value −0.31; P = 0.01 ), PSD and FEV1% (r value 0.71; P = 0.0005 ), and PSD and FVC% (r value 0.63; P = 0.003 ). Conclusions. The oxygen supply alterations might determine hypoxia of the ganglion cells causing a decrease of receptive optic nerve fiber activity. This method could be also useful to evaluate indirectly pulmonary activity of the CF disease.